(3GdYbO GdaGNQ GdMSf aj WHbGJ CcGHQ Gdjefs - (3TeS GdOjf CHh GdMSf Ydj Hf GdMSf GdNRQLj Gdjefj,J (B812 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdBNQ GdbOje, GdHGWf GdXGgQ GdMcje, GdNGdb GdQGRb GdcQje, GdHGYK GdhGQK GdQMje, GdPi Ndb hQRb hCMjG hCeGJ, haJb hQJb hChLO hCeGJ s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf, MeO GdTGQcjf ceG jMH QHfG hjQVi s
(3GdfSNI HgG MhGTs
(3Ydi UaMI GdYfhGf Jedcs
(3ai BNQ GdfSNI eWGdYI fUgG(B: (3WGdY ai gPG GdSaQ YHO Gddg Hf CejQ GdeDefjf GdeWgQ Hf eMeO Hf SdeI GdMejQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs